Evaluation of Intraocular Lens Rotational Stability in a Multicenter Clinical Trial - Vukich JA (Dove Medical Press, 2021)
John A Vukich,1 Robert E Ang,2 Benjamin JK Straker,3 Devi Priya Janakiraman,3 Pamela J Smith,3 Juan F Batlle,4 Kevin L Waltz1 1Ophthalmic Research Consultants, Indianapolis, IN, USA; 2Asian Eye Institute, Makati City, Philippines; 3Johnson & Johnson Surgical Vision, Inc, Santa Ana, CA, USA; 4Laser Center, Santo Domingo, Dominican RepublicCorrespondence: Devi Priya JanakiramanJohnson & Johnson Surgical Vision, 1700 East St. Andrew Place, Santa Ana, CA 92705, USATel +1 714-247-8429Fax +714-247-8784Email djanaki1@its.jnj.comPurpose: To evaluate the postoperative rotational stability of two prototype intraocular lens (IOL) designs (subsequently termed version 1 and version 2).Patients and Methods: A prospective, multicenter, randomized, paired-eye, 6-month study evaluated the version 1 and version 2 IOLs. Results were compared with a control IOL (TECNIS® toric 1-piece monofocal IOL) evaluated in a separate, similarly designed study. Participants aged ≥ 22 years and scheduled to undergo bilateral cataract extraction were randomly assigned 1:1 to receive the version 1 or version 2 IOL in the first operative eye; the alternate test IOL was then implanted in the second operative eye.Results: Mean absolute IOL rotation at postoperative week 1 was the primary effectiveness end point. Additional end points included the percentage of eyes with postoperative IOL rotation > 5°/> 10°, direction of lens rotation, surgeon-reported ease of IOL handling during implantation, and safety. At postoperative week 1, mean (±standard deviation) absolute IOL rotation was significantly lower for both version 1 and version 2 versus control (0.88° [± 0.94] and 0.71° [± 0.69] vs 2.24° [± 3.21], respectively; both P < 0.001). For both study lenses, absolute rotation was < 5° for all eyes at postoperative week 1, and no cases of rotation > 10° were observed at any postoperative time point. From postoperative week 1 onward, version 2 had a statistically significant clockwise bias in the direction of rotation (P = 0.03); similar findings were observed for version 1. Surgeons reported acceptable ease of IOL handling during implantation for both version 1 and version 2. No device-related adverse events were reported.Conclusion: Both the version 1 and version 2 IOLs, each with frosted, squared haptics, demonstrated improved postoperative rotational stability compared with a control lens without frosted haptics. Because version 2 had the same overall geometry as the current TECNIS toric IOL, this design was selected for commercialization.Trial Registration: German Clinical Trials Register, DRKS00015287.Keywords: astigmatism, cataract, IOL rotation, surgery, toric IOL